2019
DOI: 10.1021/acs.iecr.9b01876
|View full text |Cite
|
Sign up to set email alerts
|

Porous PdO-Flower Induced by Nanomicrostructure on Monolith with Traditional Immersion-Pyrolysis Technique for Hydrogenation

Abstract: Monolith catalysts fabricated with the immersion-pyrolysis technique suffer the uncontrollable morphology of active component, leading to low conversion and reaction rates. Herein, we propose a strategy by introducing Co3O4 nanomicrostructure on Ni foam to induce the construction of porous flower-like PdO morphology. Investigations revealed the flower structure s originally formed during the solvent evaporation after immersing Co3O4/Ni in PdCl2 solution. The nanomicrostructure also restrained the spontaneous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…This indicated that the Al 2 O 3 coatings by ED have greater advantages for the improvement of the loading and dispersion of the active component Pd. The comparisons of turnover frequency (TOF) values of the catalysts by SC and ED of Al­(NO 3 ) 3 and Al 2 O 3 electrolytes in this work and PdO/Co 3 O 4 /Ni foam catalysts in the literature are summarized in Table S1. The order of TOF values of the catalysts in the MPB was ED of Al 2 O 3 > ED of Al­(NO 3 ) 3 > SC, which was consistent with the results of the catalyst activity.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This indicated that the Al 2 O 3 coatings by ED have greater advantages for the improvement of the loading and dispersion of the active component Pd. The comparisons of turnover frequency (TOF) values of the catalysts by SC and ED of Al­(NO 3 ) 3 and Al 2 O 3 electrolytes in this work and PdO/Co 3 O 4 /Ni foam catalysts in the literature are summarized in Table S1. The order of TOF values of the catalysts in the MPB was ED of Al 2 O 3 > ED of Al­(NO 3 ) 3 > SC, which was consistent with the results of the catalyst activity.…”
Section: Results and Discussionmentioning
confidence: 99%